Natural Transformation of Plasmid DNA in Escherichia coli in Sterilized Soil Column - Mahabub-Uz-Zaman, M; Ahmed, Zia Uddin (Bangladesh Journal of Microbiology, 2010)
The present study was carried out to assess transformability of natural and laboratory strains of Escherichia coli by plasmid DNA under different transformation conditions in sterilized soil column. Transformation experiments were carried out in laboratory conditions and in sterile soil columns with CaCl2-treated competent cells and non-competent cells at log phase and stationary phase of growth using the broad host range plasmid pUC18. In soil column experiments, transformants were obtained after CaCl2 induced competence in both E. coli K12 DH5α and strain BM09 in the frequency of 10-8 to 10-9. In natural transformation assays, transformants appeared only in log phase cells of strain DH5α at a lower frequency (5.0 x 10-9), and in CaCl2-competent BM09 cells, but not in fresh cells. Thus the major limiting factor for natural transformation in environmental E. coli in soil column is probably the absence of a competent state. The significance of this finding has been discussed with respect to generally observed lower antibiotic resistance in environmental E. coli isolates from aquatic sources. Keywords: Natural transformation; Plasmid DNA; Escherichia coli; Competent state DOI: http://dx.doi.org/10.3329/bjm.v25i1.4856 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 49-52